Wide‐Bandgap Nickel Oxide with Tunable Acceptor Concentration for Multidimensional Power Devices - Yunwei Ma; Yuan Qin; Matthew Porter; Joseph Spencer; Zhonghao Du; Ming Xiao; Boyan Wang; Yifan Wang; Alan G. Jacobs; Han Wang; Marko Tadjer; Yuhao Zhang (Advanced Electronic Materials)
Abstract Multidimensional power devices can achieve performance beyond conventional limits by deploying charge‐balanced p‐n junctions. A key obstacle to developing such devices in many wide‐bandgap (WBG) and ultra‐wide bandgap (UWBG) semiconductors is the difficulty of native p‐type doping. Here the WBG nickel oxide (NiO) as an alternative p‐type material is investigated. The acceptor concentration (NA) in NiO is modulated by oxygen partial pressure during magnetron sputtering and characterized using a p‐n+ heterojunction diode fabricated on gallium oxide (Ga2O3) substrate. Capacitance and breakdown measurements reveal a tunable NA from < 1018 cm−3 to 2×1018 cm−3 with the practical breakdown field (EB) of 3.8 to 6.3 MV cm−1. This NA range allows for charge balance to n‐type region with reasonable process latitude, and EB is high enough to pair with many WBG and UWBG semiconductors. The extracted NA is then used to design a multidimensional Ga2O3 diode with NiO field‐modulation structure. The diodes fabricated with two different NA both achieve 8000 V breakdown voltage and 4.7 MV cm−1 average electric field. This field is over three times higher than the best report in prior multi‐kilovolt lateral devices. These results show the promise of p‐type NiO for pushing the performance limits of power devices.